Role of fluid injection in the evolution of fractured reservoirs. (June 2016) - Berryman, James G.
Abstract: A survey is provided of some of the better known examples of quantitative results during fluid injection on number, quality, and weakening effects for fractures in earth reservoirs along with some comparisons to either well-known or better-known theories of both fracture arrival and/or new growth of existing fractures through both fluid injection and stress application. The detailed analyses presented focus on reservoirs having (at worst) orthotropic symmetry.